Why and When Do Good Soldiers Behave Unethically? Introducing Conservation of Resources Theory to Explain the Curvilinear Effects of Organizational Citizenship Behavior - Xu, Fangfang; Xu, Shiyong; Zhu, Jinqiang; Zhou, Jinyi; Zhang, Bainan; Yang, Chunmeng (Frontiers in Psychology, 2021)
Previous research about organizational citizenship behavior and counterproductive work behavior has produced contradictory results. Drawing from the conservation of resources theory, the present study tries to explain the contradictory findings by examining the curvilinear relationship between organizational citizenship behavior and counterproductive work behavior. Using data collected at three time points from 426 employees and 110 supervisors in Chinese companies, data analysis shows that OCB has an inverted U-shaped relationship with counterproductive work behavior. The results also demonstrate that citizenship fatigue mediates the relationship between organizational citizenship behavior and counterproductive work behavior, perceived organizational support moderates the relationship between organizational citizenship behavior and citizenship fatigue. In addition, perceived organizational support moderates the mediating effect of citizenship fatigue in the inverted U-shaped curvilinear relationship between organizational citizenship behavior and counterproductive work behavior. This mediating effect is stronger under conditions of low perceived organizational support than high perceived organizational support. The findings present a complementary explanation of the conflicting relationships between organizational citizenship behavior and counterproductive work behavior.